(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The union territory of Jammu and Kashmir is the heavenly abode with diversified social setting that hones the multitude of cultures and ethnic communities. In this milieu, the study has explored and analyzed the socio-economic circumstances of tribal communities of Jammu and Kashmir and the role of variety of policy measures and non-state actors for their socio-economic upliftment. The study has adopted qualitative approach and secondary data sources to explore the socio-economic profile of tribals in Jammu and Kashmir and also discusses the policies and programs for STs in Jammu and Kashmir. In this context, the findings of the study have revealed that Scheduled Tribal communities in the union territory of Jammu and Kashmir are socially and economically impoverished, discriminated, and alienated. However, the planned Tribal education has taken on added significance in light of the country's intended growth in human resources. Education is critical for social and economic advancement, and the amount of education impacts career opportunities. Furthermore, the data from the census 2011 and 2001 has revealed that education and literacy rates of the Scheduled Tribes of Jammu and Kashmir are significantly lower than those of tribes at the national level. Unemployment and lack of basic infrastructure seem to be key obstacles to obtaining an education and an effective career opportunity.